Pharmacological mechanism and clinical application of ciprofol - Zhou, Jianshun; Wang, Lifeng; Zhong, Zhaoying; Yuan, Lei; Huang, Jinhua; Zou, Ping; Cao, Xiaohui; Peng, Donglan; Liao, Baozhen; Zeng, Jianqiang (Frontiers in Pharmacology, 2025)
Propofol has become one of the most commonly used anesthetic agents because of its good sedative effects, rapid onset, and fast metabolism. However, its associated respiratory and circulatory depression and injection pain make it difficult for patients to tolerate. Ciprofol, which is structurally similar to propofol but has an additional cyclopropyl group, is less likely to impact respiratory and circulatory function and cause injection pain, highlighting its potential for clinical application. Currently, as research on Ciprofol is still in the exploratory stage, its clinical application is limited because its underlying mechanisms are not yet fully understood. The aim of this article is to review the pharmacological mechanisms of propofol, hypothesize the primary pharmacological effects and potential adverse reactions of Ciprofol, and summarize its current clinical application status, with the goal of providing a reference for future clinical use.